2017
DOI: 10.1016/j.biocontrol.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Resistant and susceptible tomato genotypes have direct and indirect effects on Podisus nigrispinus preying on Tuta absoluta larvae

Abstract: h i g h l i g h t s Resistant plant genotypes may affect natural enemies directly and indirectly. Resistant tomato plants directly affected P. nigrispinus development and behavior. The negative effects were associated with density and types of glandular trichomes. Using P. nigrispinus and resistant tomato could be antagonistic for T. absoluta control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
0
6
0
2
Order By: Relevance
“…A plant's allelochemicals may influence, directly and indirectly, a predator's performancedirectly, through the presence of physical structures such as trichomes exuding chemicals (Bottega et al, 2017) or through the uptake of nutrients and water from the plant (De Clercq & Degheele, 1992;Wiedenmann et al, 1996;De Clercq et al, 2000), or indirectly, through their prey, which may sequester these plant compounds and use them against natural enemies (Weiser & Stamp, 1998;Chaplin-Kramer et al, 2011;Reudler et al, 2015). Once ingested by herbivorous insects, a sequestered substance may be reabsorbed by the intestinal membrane, transported to the hemolymph, and deposited in various body parts, becoming toxic or unpalatable to its natural enemies (Nishida, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A plant's allelochemicals may influence, directly and indirectly, a predator's performancedirectly, through the presence of physical structures such as trichomes exuding chemicals (Bottega et al, 2017) or through the uptake of nutrients and water from the plant (De Clercq & Degheele, 1992;Wiedenmann et al, 1996;De Clercq et al, 2000), or indirectly, through their prey, which may sequester these plant compounds and use them against natural enemies (Weiser & Stamp, 1998;Chaplin-Kramer et al, 2011;Reudler et al, 2015). Once ingested by herbivorous insects, a sequestered substance may be reabsorbed by the intestinal membrane, transported to the hemolymph, and deposited in various body parts, becoming toxic or unpalatable to its natural enemies (Nishida, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…George and Lapointe 31 suggested that morphological and physiological barriers associated with access to the phloem sieve elements, poor nutritional quality, and deterrent chemical compounds may be involved in P. trifoliata resistance to D. citri . Trichome density is a morphological trait that may serve as a defense against insect herbivory 33–36 thereby interfering with insects landing, walking, and feeding on plant surfaces 37,38 . In Citrus and Poncirus , trichomes have little to no role in deterring oviposition by D. citri 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Trichome density is a morphological trait that may serve as a defense against insect herbivory [33][34][35][36] thereby interfering with insects landing, walking, and feeding on plant surfaces. 37,38 In Citrus and Poncirus, trichomes have little to no role in deterring oviposition by D. citri. 39 However, to the best of our knowledge, the influence of trichome density on the shoots of Citrinae species on D. citri development has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…As estratégias de manejo para o controle da T. absoluta incluem táticas de controle cultural, varietal e biológico (BOTTEGA et al, 2017;KAOUD, 2014;CAPARROS MEGIDO;HAUBRUGE;VERHEGGEN, 2013;ZAPPALÀ et al, 2012).…”
Section: Introductionunclassified